Launching Global Lung Function Initiative reference values in Belgium: tips and tricks. Issue 2 (2nd August 2018) - Derom, Eric; Liistro, Giuseppe; Oostveen, Ellie; Marchand, Eric; Bedert, Lieven; Peché, Rudi; Janssens, Wim
Pulmonary function tests are pure physiological measurements. Spirometry allows the clinician to label lung diseases as either obstructive or restrictive, the latter requiring confirmation with static lung volume measurements. Transfer factor of the lung for carbon monoxide ( T LCO ) informs the clinician about the gas exchange properties of the respiratory system. A prerequisite to distinguish normal from abnormal data is the availability of accurate reference values as well as their lower and higher limits of normality. Choosing the correct set of reference values is crucial to discriminate health from disease in the individual and will influence any further medical processes. Indeed, results from one given subject may fall within the normal range using one equation while being abnormal using another [1–5]. The availability of accurate reference values is not only important in the diagnostic work-up and management of a single patient, it also leads to a better understanding of the global burden of lung disease, and allows a statistically correct estimation of the degree of impairment and disability in occupational medicine. A model consisting of a motivated working group that identified the different stakeholders to convince them, through education, over the Global Lung Function Initiative reference values has appeared to be successful in implementing these in Belgium http://ow.ly/Q21630kuE1N